Analisis Permintaan Tenaga Kerja Sektor Manufaktur Menengah dan Besar di Indonesia Tahun 2010-2014 - Antonius Ivan Hertomo (Diponegoro Journal of Economics, 2020)
This study aims to analyze the labor demand in the medium-large Indonesian manufacturing industry over the period of 2010-2014. This study uses secondary data in the form of time series data and cross section data, obtained from Indonesian Central Bureau of Statistics (BPS). This study uses panel data method with Random Effect estimation model. Estimates are carried out at firm level with a balanced panel data model. The number of observations used in this study was 18.795, with a sample of 3.759 firms in a period of five years. This study also included the industrial concentration level calculated in the industry level and industrial location as a dummy variable. The results of this study shows that independent variables, such as output, capital, industrial location, wages, and efficiency are significantly influence the labor demand. Meanwhile, industrial location variable doesn’t significantly influence the labor demand. Output and capital variables have positive influence on the labor demand while wages, industrial concentration level, efficiency and industrial location variables have negative influence on labor demand.